2023
DOI: 10.3390/foods12132593
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grape Pomace Flour as Nutritive Ingredient for Enriched Durum Wheat Pasta with Bioactive Potential

Abstract: In this study, grape pomace is used as an ingredient to fortify pasta. The grape pomace phenolic component is highly accessible and available for metabolization in the human gut. Hence, grape pomace can be exploited as a source of polyphenols and fiber for sustainable and dietary beneficial food production. Analyses of soluble and bound phenols and volatile compounds in raw and cooked pasta were performed. In the uncooked pasta fortified with pomace, the content of soluble and bound phenolic molecules increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The predominant fraction of volatile compounds in both the control and enriched pasta was aldehydes, mainly acetaldehyde and 2-methylpropanal. Similarly, other authors have indicated that aldehydes are the predominant fraction of the volatile compounds of pasta [50,51]. However, the content of these compounds decreased progressively in relation to the percentage of both additives used to enrich the pasta, particularly with the use of freeze-dried cherry pomace.…”
Section: Effect Of Freeze-dried Red Potato Pulp and Cherry Pomace On ...mentioning
confidence: 56%
See 1 more Smart Citation
“…The predominant fraction of volatile compounds in both the control and enriched pasta was aldehydes, mainly acetaldehyde and 2-methylpropanal. Similarly, other authors have indicated that aldehydes are the predominant fraction of the volatile compounds of pasta [50,51]. However, the content of these compounds decreased progressively in relation to the percentage of both additives used to enrich the pasta, particularly with the use of freeze-dried cherry pomace.…”
Section: Effect Of Freeze-dried Red Potato Pulp and Cherry Pomace On ...mentioning
confidence: 56%
“…In addition, pasta enriched with freeze-dried cherry pomace was characterized by a high content of acetaldehyde, 2-methylpropanal, benzaldehyde, γ-butyrolactone and 4-ethylguaiacol. Most of these compounds are degradation products of the relevant amino acids and sugars [51,52]…”
Section: Effect Of Freeze-dried Red Potato Pulp and Cherry Pomace On ...mentioning
confidence: 99%
“…In other grape varieties, specifically Cabernet Sauvignon and Sauvignon Blanc, the protein levels were similarly close, recorded at 10.8% and 7.2%, respectively [39]. These protein levels are similar to those in wheat flour [45], making grape pomace flour a suitable gluten-free alternative for celiacs, potentially improving nutritional quality.…”
Section: Nutritional Composition Of Grape Pomace Flourmentioning
confidence: 68%
“…Hedonic scale was used to carry out sensory analysis and the results showed that pasta sample fortified with 3 % dietary fibre and 5 % soy flour displayed best attributes. Gerardi and team (2023) utilized GP for fortification of pasta. In case of uncooked GP fortified pasta, the bound and soluble phenolic content increased significantly.…”
Section: Applications Of Selected Fruit Pomaces In Food Enrichmentmentioning
confidence: 99%